Subthalamic Nucleus Deep Brain Stimulation Does Not Modify the Functional Deficits or Axonopathy Induced by Nigrostriatal α-Synuclein Overexpression. Issue 1 (December 2017) - Fischer, D.; Manfredsson, Fredric; Kemp, Christopher; Cole-Strauss, Allyson; Lipton, Jack; Duffy, Megan; Polinski, Nicole; Steece-Collier, Kathy; Collier, Timothy; Gombash, Sara; Buhlinger, Daniel; Sortwell, Caryl
Abstract Subthalamic nucleus deep brain stimulation (STN DBS) protects dopaminergic neurons of the substantia nigra pars compacta (SNpc) against 6-OHDA and MPTP. We evaluated STN DBS in a parkinsonian model that displays α-synuclein pathology using unilateral, intranigral injections of recombinant adeno-associated virus pseudotype 2/5 to overexpress wildtype human α-synuclein (rAAV2/5 α-syn). A low titer of rAAV2/5 α-syn results in progressive forelimb asymmetry, loss of striatal dopaminergic terminal density and modest loss of SNpc dopamine neurons after eight weeks, corresponding to robust human-Snca expression and no effect on rat-Snca, Th, Bdnf orTrk2 . α-syn overexpression increased phosphorylation of ribosomal protein S6 (p-rpS6) in SNpc neurons, a readout of trkB activation. Rats received intranigral injections of rAAV2/5 α-syn and three weeks later received four weeks of STN DBS or electrode implantation that remained inactive. STN DBS did not protect against α-syn-mediated deficits in forelimb akinesia, striatal denervation or loss of SNpc neuron, nor did STN DBS elevate p-rpS6 levels further. ON stimulation, forelimb asymmetry was exacerbated, indicating α-syn overexpression-mediated neurotransmission deficits. These results demonstrate that STN DBS does not protect the nigrostriatal system against α-syn overexpression-mediated toxicity. Whether STN DBS can be protective in other models of synucleinopathy is unknown.